A Topical Desiccant Agent in Association with Manual Debridement in the Initial Treatment of Peri-Implant Mucositis: A Clinical and Microbiological Pilot Study - Giorgio Lombardo; Annarita Signoriello; Giovanni Corrocher; Caterina Signoretto; Gloria Burlacchini; Alessia Pardo; Pier Francesco Nocini (MDPI AG, 2019)
In patients presenting mucositis, effective sub-gingival debridement is crucial to prevent peri-implantitis. The aim of this randomized study was to assess the three-month (T1) effects of a locally delivered liquid desiccant agent with molecular hygroscopic properties, in association with manual debridement, at sites with peri-implant mucositis. Twenty-three patients presenting at least one implant with no radiographically detectable bone loss, a pocket probing depth (PPD) ≥ 4 mm, and bleeding on probing (BOP), were included. At baseline (T0), patients were randomly assigned to receive the aforementioned desiccant agent before debridement (Test-Group), or a Chlorhexidine 1% disinfectant gel after debridement (Control-Group). Treatments were repeated after seven and 14 days. Peri-implant soft tissue assessment [PPD, BOP, Modified Bleeding Index (mBI), Visible Plaque Index (VPI), and Modified Plaque Index (mPLI)] and microbial sampling were performed at T0 and T1. At T1 the Test-Group presented significantly greater reductions for BOP, mBI, VPI, and mPLI. Concerning the deepest sites of the treated implants, both groups showed statistically significant reductions for BOP and mBI between T0 and T1. Furthermore, the Test-Group exhibited a significant decrease in anaerobic bacteria. Despite these valid outcomes, a complete resolution of the inflammatory conditions was not achieved by any of the groups.